2015
DOI: 10.1007/s11420-014-9423-7
|View full text |Cite
|
Sign up to set email alerts
|

A Report on Three Consecutive Cases using Computer Tomography 3D Preoperative Planning for Conversion of Arthrodesed Hips to Total Hip Replacements

Abstract: CT-based preoperative 3D planning could be a powerful guidance tool for conversion of arthrodesed hips to THAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Another study by Richards and Duncan reported significantly worse clinical outcomes and patient satisfaction as well as higher complication rates compared to common primary and revision THA [23]. Regardless of the higher complication rate, patient satisfaction and postoperative outcomes were generally good [6,8,22]. Regarding surgical techniques, it was difficult to secure adequate visualization of the surgical field due to the contracture of the soft tissue and a lack of hip movement [7,21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study by Richards and Duncan reported significantly worse clinical outcomes and patient satisfaction as well as higher complication rates compared to common primary and revision THA [23]. Regardless of the higher complication rate, patient satisfaction and postoperative outcomes were generally good [6,8,22]. Regarding surgical techniques, it was difficult to secure adequate visualization of the surgical field due to the contracture of the soft tissue and a lack of hip movement [7,21].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding surgical techniques, it was difficult to secure adequate visualization of the surgical field due to the contracture of the soft tissue and a lack of hip movement [7,21]. Additionally, the level of the neck cut and the original acetabulum were difficult to identify due to the deformity of the pelvis and fused proximal femur [6][7][8]. Malpositioning of the femur, which included a high femoral neck-shaft angle, unusual anteversion, and flexion-abduction contracture, made the preparation of the femur difficult [6,8,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our opinion is that advantages of 3D can be shown clearly when treating more complicated cases, as Kuroda et al demonstrated in their study about three consecutive cases for conversion of arthrodesis hips to total hip replacements. 15…”
Section: Innovation In Tha Templatingmentioning
confidence: 99%